Implementasi Metode Algoritma Genetika Pada Penentuan Menu Makanan Untuk Membentuk Berat Badan Ideal - Christopher Nanda Jonathan (Jurnal Teknologi Informasi dan Terapan, 2019)
Human need balanced nutrition to grow up. It contained various nutrients namely energy, protein, vitamins, and minerals. Data from the Ministry of Health, the proportion of overweight in adults above 18 years old on 2018 amounted to 13%, while data from Basic Health Research mentions that adults with nutritional deficiencies amounted to 12.6%. This shows that many adults do not pay attention to the food with balanced nutrition that can lead to obesity and nutritional deficiencies. To prevent this, it can be done by eating healthy food that contains enough calories. Someone needs different calories according to the age, height, weight, gender and physical activity. To optimize the level of calory that being consumed daily, we use Genetic Algorithm to obtain more menus with higher calory, the menu will be divided into breakfast, lunch, and dinner, in accordance to the recommended nutritional needs. From this study using Genetic Algorithms, there is an average increase in the number of calories by 88 kcal, from 1037 kcal to 1123 kcal, and there is one chromosome that satisfies the recommended calorie requirement, which is 1,849 kcal.